Complete Cranial Iliac Osteotomy to Approach the Lumbosacral Foramen - Dyall, Barbara; Schmökel, Hugo (Frontiers in Veterinary Science, 2017)
An approach using a complete cranial iliac osteotomy to access the lumbosacral foramen in dogs from lateral was developed using cadavers and applied in a clinical patient with degenerative lumbosacral stenosis. The foraminal enlargement in the cadavers and the patient was documented on postoperative CT scans. The preoperative CT scan of the patient showed moderate cranial telescoping of the sacral roof and a moderate central disk protrusion, leading to moderate to severe compression of the cauda equina. In addition, there was lateral spondylosis with consequential stenosis of the right lumbosacral foramen. The right L7 nerve had lost its fat-attenuation and appeared thickened. After a routine L7S1 dorsal laminectomy with a partial discectomy, a complete cranial iliac osteotomy was performed, providing good access to the lumbosacral foramen and the adhesions around the proximal L7 nerve caudoventral of the foramen. The osteotomy was stabilized with a locking plate and a cerclage wire. The dog recovered well from the procedures, and was discharged from the hospital after 36 hours walking normally. Eight and 16 weeks later, the signs of the DLSS had markedly improved.From these data, it can be concluded that the complete cranial iliac osteotomy is a useful approach to the lumbosacral foramen and intervertebral disc in selected patients with degenerative lumbosacral stenosis, giving good access to the structures around the lumbosacral foramen.